Latent Profiles of Deceased Organ Donation Registrants and Nonregistrants in the United States - Ari P. Kirshenbaum; Brendan Parent; Landry Goodgame Huffman; Virginia Kelsey; Michael J. Sofis (Journal of Transplantation)
Deceased organ donation is the greatest source of transplantable whole organs, but registration rates are a limiting factor because they remain low among certain populations. A stratified, nonprobability survey was used to identify population characteristics associated with nonregistration in the United States (N = 11,083). Latent profile analysis (LPA) was used to identify multivariate patterns of demographic, socioeconomic, and health-related factors associated with registration. LPA yielded three distinct profiles, which all reported similar average percentages of driver’s license possession, medical insurance coverage, and income, indicating that profiles were not distinguished by these variables. Meaningful differences across the profiles included access to healthcare services, satisfaction with those services, general health and well-being, and age; those who are both healthy and young (mean age = 25.9 years) reported the lowest percentage of organ donation registration (35.3%). For this group, 71.48% listed either low priority or distrust in the donation process as the top reasons for nonregistration. Importantly, age as a standalone variable was not uniformly associated with donation and was conditionally dependent upon health status; poorer health in young adults was associated with greater registration. These findings reveal previously unidentified opportunities for tailoring donor registration campaigns to populations with a high potential for registration behavior change.